Exploring students' preference of the role of educators in asynchronous online discussions - Mahmud, Rosnaini; Ismail, Mohd Arif; Nawawi, Mokhtar (2009)
The development and advancement of Information and Communication Technology has caused the creation of a borderless world. In the field of education, a borderless world means classrooms without walls where teaching and learning is conducted in a virtual environment. In contrast of their role as ‘a sage on stage’ in conventional schooling, educators now have multiple roles to play, particularly to facilitate online learning. Online technologies have afforded educators and students the luxury to communicate and interact synchronously or asynchronously in a virtual learning environment. As such, the role of the online educator is vital in enhancing students’ learning particularly where asynchronous computer-mediated-communication (ACMC) is concern. Thus, the aim of this paper is to present the findings of a study that explored: (i) the educator’s role preferred by students and (ii) students’ perception toward asynchronous online discussions in terms of interest, inhibition and assessment. A total of 90 students in a Malaysian college were the research respondents. The instruments used to measure educators’ role and students’ perception were the students’ posting on the discussion board and interview protocols. Findings showed that the most preferred educators’ role was as the content provider, followed by the role as the course builder. Least preferred was the role as the course facilitator. Majority of the students perceived that ACMC had both advantages and disadvantages. However, students were found to prefer teacher-centered learning approach much more than to participate in collaborative learning. This interesting finding calls for more in depth study that examine the factors that contribute to students’ learning and participation in online learning virtual environment.